2014
DOI: 10.1111/bjd.13216
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of cutaneous warts in elementary school children and the ubiquitous presence of wart-associated human papillomavirus on clinically normal skin

Abstract: Cutaneous wart-associated HPV types were highly prevalent in primary school children, but did not correlate with the HPV types in warts. In contrast to the existing literature, HPV1 was frequently detected on clinically normal skin but was much less frequent in warts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
62
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 15 publications
3
62
1
Order By: Relevance
“…In contrast to previous studies [52, 53], multiple HPV types were detected in 15/22 (68.2%) cutaneous warts and, interestingly, HPV1 was concurrently detected in all HPV63-positive samples (Table 3). Kohler et al [54] have shown that, in cutaneous warts with mixed infections, clinically latent HPV infections can be discerned from a productive infection with a cutaneous wart–associated HPV type based on the viral load determination.…”
Section: Resultscontrasting
confidence: 87%
See 3 more Smart Citations
“…In contrast to previous studies [52, 53], multiple HPV types were detected in 15/22 (68.2%) cutaneous warts and, interestingly, HPV1 was concurrently detected in all HPV63-positive samples (Table 3). Kohler et al [54] have shown that, in cutaneous warts with mixed infections, clinically latent HPV infections can be discerned from a productive infection with a cutaneous wart–associated HPV type based on the viral load determination.…”
Section: Resultscontrasting
confidence: 87%
“…The relatively low prevalence of HPV1- and HPV63-induced cutaneous warts in our study could be explained by the cutaneous warts’ locations, patient selection, and distinct clinical and histopathological manifestations of infection with Mu -PVs in different age groups [15, 16, 53]. Namely, HPV1-induced cutaneous warts are more prevalent in younger children [53], whereas all cutaneous wart samples in this study were obtained from adult patients, in whom Alpha -PVs are the usual etiological agents [54]. In addition, the majority of cutaneous warts were obtained from hands, whereas HPV1 and HPV63 typically cause plantar warts [16].…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…In a recent study performed in elementary schools in the Netherlands, HPV-57 DNA was detected in 14% of all warts. In contrast, in swabs taken from healthy skin in the same group, HPV-57 was a rare finding, although 80% of all tested children had at least one HPV-positive non-wart swab [15]. In line with these results, HPV genotyping in future KP cases has to reveal whether detection of HPV DNA, especially HPV-57, is a common finding favoring the idea that KP might reflect a particular type of viral papilloma.…”
Section: Discussionmentioning
confidence: 99%